Publisher Correction: Glacial–interglacial Nd isotope variability of North Atlantic Deep Water modulated by North American ice sheet - Ning Zhao (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.